HUBUNGAN ANTARA KECAKAPAN KOMUNIKASI FRONTLINER DENGAN KEPUASAN NASABAH PT. BANK TABUNGAN NEGARA - Radhityo Ryandhika Rakadiputra; Agus Naryoso (Interaksi Online, 2019)
Information becomes one of the important things within bank institutions. The fulfillment of information is one part in the service process. Information was originally came from the frontliner. The role of frontliner communication is well needed in the service process with the purpose of creating customer satisfaction. Services are not just a fulfillment of customers’ needs, but also must be able to satisfy customers far above customer expectations. Communication skills becomes one of the factors that affects the quality of service and the satisfaction level of customers. With good communication skills it is expected to create customer satisfaction. The purpose of the study was to figure out the relationship between frontliner communication skills with the satisfaction of PT Bank Tabungan Negara customers. The study used descriptive quantitative research methods. Data collection techniques use the method of spreading questionnaires. The analysis used is cross tabulation analysis. The data received from the questionnaires processed by categorizing the overall aspects of communication skills and customer satisfaction resulting in data showing that out of a total of thirty (30) respondents were known as forty percent (40%) respondents stated that frontliners had good communication skills and customers were satisfied, three point three percent (3.3%) respondents stated that frontliners had good communication skills and customers were very satisfied, six point seven percent (6.7%) of respondents stated that frontliners had excellent communication skills and customers were satisfied, and fifty percent (50%) of respondents stated that frontliners had excellent communication skills and customers were very satisfied. Based on cross-tabulation analysis that has been done, it is known that customer assessment of the level of communication skills shared by the PT Bank Tabungan Negara frontliners is in line with the level of satisfaction felt by customers. In other words, the better customer assessment of communication skills possessed by the frontliners of PT Bank Tabungan Negara, the customers are increasingly satisfied. It can be concluded that frontliner communication skills are related to customers satisfaction of PT Bank Tabungan Negara.